Survival analysis - Guo, Shenyang (New York ; Oxford : Oxford University Press, 2010)
Survival analysis is a class of statistical methods for studying the occurrence and timing of events. With clearly written summaries and plentiful examples, this pocket guide will put this important statistical tool in the hands of many more social work researchers than have been able to use it before.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Event history analysis; Social sciences -- Statistical methods